Potential advantages and disadvantages of telemedicine: A literature review from the perspectives of patients, medical personnel, and hospitals - Lie Rebecca Yen Hwei; Gilbert Sterling Octavius (Journal of Community Empowerment for Health, 2021)
With the increase in the aging population around the world, the medical field is also changing in response. The number one cause of mortality in the aging population is non-communicable diseases such as diabetes mellitus, heart disease or kidney failure. Advancements in technology make it possible for diagnoses and treatments to be no longer confined physically but they can be done virtually. However, there are several drawbacks in fully utilizing telemedicine such as hesitancy from the medical personnel and unclear law requirements. In this review, we discuss the advantages and disadvantages of telemedicine from three perspectives of the patients, medical personnel, and hospitals.